FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK KOPERASI DI KOTA SEMARANG (Students' Journal of Accounting and Banking, 2015)
This study aimed to examine the effect of awareness, knowledge and understanding, and a good perception of the effectiveness of the tax system on the willingness to pay taxes on cooperatives in the city of Semarang. The population in this study is a savings and credit cooperatives in the city of Semarang. The sampling technique in this research is convinience sampling or sample was selected based on convenience. Data analysis techniques used in this research is multiple linear regression analysis. Based on the results of this study concluded that awarenesss to pay taxes, knowledge and understanding of tax laws and a good perception of the effectiveness of the tax system have a significant influence on the willingness to pay taxes.Keywords: The Willingness To Pay Taxes, Knowledge And Understanding Of Tax Regulation, Good Perception On Effectiveness Of Tax System